2016
DOI: 10.1021/acs.joc.6b01102
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous-Medium Carbon–Carbon Bond-Forming Radical Reactions Catalyzed by Excited Rhodamine B as a Metal-Free Organic Dye under Visible Light Irradiation

Abstract: The utility of rhodamine B as a water-soluble organic photocatalyst was studied in the cascade radical addition-cyclization-trapping reactions under visible light irradiation. In the presence of (i-Pr)2NEt, the electron transfer from the excited rhodamine B to perfluoroalkyl iodides proceeded smoothly to promote the carbon-carbon bond-forming radical reactions in aqueous media. When i-C3F7I was employed as a radical precursor, the aqueous-medium radical reactions proceeded even in the absence of (i-Pr)2NEt. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 131 publications
0
19
0
Order By: Relevance
“…[11] Several organic molecules have proven successful as visible light PCs for small molecule and polymeric transformations. [12] The majority of these organic PCs, such as Eosin Y, [13] rhodamine dyes, [14] acridinium salts, [15] perylene diimides, [16] and carbazolyls [17] are excited state oxidants and operate through a reductive quenching cycle. Although a few strongly reducing organic PCs exist, [18] many do not absorb visible light.…”
mentioning
confidence: 99%
“…[11] Several organic molecules have proven successful as visible light PCs for small molecule and polymeric transformations. [12] The majority of these organic PCs, such as Eosin Y, [13] rhodamine dyes, [14] acridinium salts, [15] perylene diimides, [16] and carbazolyls [17] are excited state oxidants and operate through a reductive quenching cycle. Although a few strongly reducing organic PCs exist, [18] many do not absorb visible light.…”
mentioning
confidence: 99%
“…Although there is tentative evidence for an interaction between MCL-1 and BCL-x L 54 , the observation that higher concentrations of TAMRA-RTA 2 (500 µM) led to more non-specific labelling of BCL-x L ( Supplementary Fig. 34) suggest this trace labelling results from the ability of TAMRA itself to act as non-targeted photocatalyst 46,47 . Indeed, when labelling was performed with Ac-RTA instead, ESI-MS analysis did not reveal any Ru(II) (bpy) 3 -NOXA-B 1-mediated SET labelling (nor degradation) of BCL-x L ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the labelled mixture using in-gel fluorescence indicated that ruthenium-modified peptide 1, fluorescent RTA 2 and visible light irradiation were all necessary for efficient labelling of MCL-1. A small amount of background labelling of MCL-1 occurred in the absence of 1, possibly due to the ability of the rhodamine dye in 2 to act as a photoredox catalyst 46,47 (lane 3, Fig. 2c; more clearly seen when larger amounts of protein were loaded onto the SDS-PAGE gel: Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The utility of rhodamine B as a water-soluble photocatalyst was demonstrated in the aqueousmedium carbon-carbon bond-forming radical reactions [47]. In the presence of (i-Pr) 2 NEt as a reductive quencher, the rhodamine B-catalyzed reaction of alkene 34 with i-C 3 F 7 I in H 2 O proceeded smoothly to give the product 35 in 90% yield (Figure 14).…”
Section: Visible-light Photocatalysis Of Carbon-based Materialsmentioning
confidence: 99%